Post-marketing safety concerns with dolutegravir: a pharmacovigilance study based on the FDA adverse event reporting system database - Juan Su; Long He; Menglei Wang (Frontiers in Pharmacology)
Background and aimsAntiretroviral therapy (ART) based on dolutegravir (DTG) has emerged as a critical component in the treatment of HIV infection and is widely utilized in clinical practice. However, the existing post-marketing pharmacovigilance studies on DTG are incomplete; therefore, this study aims to comprehensively analyze the adverse events (AEs) related to DTG by utilizing the FDA Adverse Event Reporting System (FAERS) database.MethodsThis study includes adverse event reports from the fourth quarter of 2013 to the fourth quarter of 2024 in the FAERS database. Four disproportionality analysis methods were employed for adverse event signal mining: Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Empirical Bayesian Geometric Mean (EBGM). Additionally, clinical priority and time-to-onset characteristics were assessed.ResultsA total of 13,007 case reports were collected with DTG as the primary suspected (PS) drug, including 32,383 AEs. Observed disproportionate associations with the use of DTG were related to pregnancy, puerperium and perinatal conditions (n = 688; ROR = 5.53, 95% CI 5.13–5.96), hepatobiliary disorders (n = 655; ROR = 2.45, 95% CI 2.27–2.65), and congenital, familial and genetic disorders (n = 550; ROR = 6.11, 95% CI 5.62–6.65). A total of 341 AE signals were identified in the overall analysis, among which 164 were rated as moderate clinical priority, with no high clinical priority signals. Notably, subgroup analyses revealed that progressive multifocal leukoencephalopathy (n = 9) in males, progressive multifocal leukoencephalopathy (n = 6) and deafness neurosensory (n = 3) in the 18–45 age group, and hepatic necrosis (n = 4) in the 46–65 age group were rated as high clinical priority. The overall onset time for all AEs exhibited an early failure pattern, with a median onset time of 74 days (IQR 19–310.5), whereas the median onset time for designated medical events (DMEs) was 59 days (IQR 12–186).ConclusionThe long-term safety of DTG requires reassessing its risk-benefit ratio. To mitigate the risk of irreversible organic damage, a structured risk management strategy is essential. This strategy should encompass restrictions on contraindicated populations, enhanced monitoring of high-risk subgroups, and the implementation of post-marketing prospective cohort studies to ensure the sustainability of antiviral therapy.